Evaluation of program activities to improve access to the city transport system for people with limited mobility - K. E. Safronov; S. M. Mochalin (Вестник СибАДИ)
The article dwells on the method of assessing realization of activities of the state program "Accessible Environment" to improve access to the environment for people with disabilities and limited mobility on the example of big cities of the Russian Federation. The unavailability of the transport system reduces the mobility and leads to discrimination on the basis of disability. Developed grade system of accessibility is directed to assess the effectiveness of program activities. There are considered the problems of using normative framework, quality certification of services’ accessibility and further ways for improving availability on the legislative level.